A IMPORTÂNCIA DA IMPLEMENTAÇÃO PRECOCE DE CUIDADOS PALIATIVOS NO TRATAMENTO ONCOLÓGICO: UMA REVISÃO INTEGRATIVA - Pereira, Martin Bensiman da Silva Fontenelle; Mendonça, Marcos Antônio (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Palliative care is provided by a multidisciplinary team to patients affected by a disease that threatens the continuity of life, when there is no prospect of a cure, also covering their families. Although its early implementation in oncologic patients has benefits such as: improved quality of life and mental health, there is still a lack of consensus in the literature. This study aims to analyze whether palliative care in the early stages of cancer promotes positive results, as well as understanding the existing difficulties for its realization in medical practice. A systematic literature review was carried out, based on the National Library of Medicine (PubMed) and the Virtual Health Library (VHL), with articles in English, published between 2015 and 2021, full texts, meta-analysis studies, controlled clinical trials, clinical trials, randomized controlled trials, observational studies. Among the 25 selected articles, 14 successfully improved the well-being of cancer patients and their families in a satisfactory way due to following all palliative treatment guidelines. The study showed that there are several advantages in early palliative care, being able to improve the quality of life of these individuals, but that there are still obstacles in this process, requiring specific approaches for each case.